Safety and efficacy of antigen-specific therapeutic approaches for multiple sclerosis: Systematic review - Öztürk, Hatice Kübra; Slanař, Ondřej; Michaličková, Danica (PloS one, 2025)
INTRODUCTION: The objective of this systematic review is to evaluate the efficacy and safety of antigen-specific tolerance-inducing therapeutic approaches (products based on peptides, DNA and T cells) versus placebo or other comparators, where possible, in adult multiple sclerosis (MS) patients. METHODS: PubMed, CINAHL, Web of Science, Cochrane and International Clinical Trials Registry Platform, ClinicalTrials.gov were searched for published and unpublished studies. Screening, critical appraisal, and data extraction for included studies were carried out by two independent reviewers. For efficacy, phase I, II and III clinical trials (randomized/non-randomized; double blind/single blind/unblinded; single-center/multicenter; single-arm/two-arm) and for safety, phase I, II and III clinical trials (randomized/non-randomized; double blind/single blind/unblinded; controlled/uncontrolled; single-center/multicenter; single-arm/two-arm) were included. Observational studies (cross-sectional studies, cohort studies, case studies/reports etc), review articles, systematic reviews, meta-analysis, preclinical and pilot studies were excluded. All included studies were critically appraised using standardized JBI tools, with no exclusions based on methodological quality. Where possible, studies were pooled in statistical meta-analysis, presented in tabular format, and accompanied by narrative synthesis. The Grading of Recommendations, Assessment, Development and Evaluation (GRADE) approach for grading the certainty of evidence. RESULTS: Search yielded 2644 results and in total 26 studies were included in the final analysis. Twelve studies were RCTs and 14 were quasi-experimental. In total, there were 1427 subjects from the RCTs, and 314 from non-RCTs. Sample size of studies ranged from 10 to 612 patients. All studies included adult patients, principally aged 18-55/65 years. Critical appraisal scores for the RCTs were in the range 31% to 92%. For quasi-experimental studies, critical appraisal scores were in the range 45% to 78%. Due to high heterogeneity of the studies, efficacy of all antigen-specific treatment remained ambiguous. For all three types of treatment, there was no statistical difference in occurrence of adverse effects (AEs) between the treatment- and placebo-related AEs (for DNA-based treatment RR was 1.06 (0.94-1.10), p = 0.334; for peptides-base treatments RR was 1.04 (0.90-1.08), p = 0.115; for T-cells-based treatments RR was 1.31 (0.97-1.76), p = 0.08). There were no differences in RR for serious AEs (SAEs) between the treatments either for DNA-based treatment (RR was 0.63 (0.25-1.58), p = 0.322) or peptide-based treatment (RR was 0.86 (0.62-1.19), p = 0.361). There were no reported SAEs for T cell-based treatments, so meta-analysis for these therapies was not performed. The most frequent AEs were local reactions to injection, such as redness, erythema, pain. DISCUSSION: Antigen-specific tolerance-inducing therapeutic approaches appeared to be safe. However, the certainty for these results was very low for SAEs in peptide- and DNA-based therapies, whereas it was low for AEs in DNA- and T cells-based therapies and moderate for AEs in peptide-based therapies. The efficacy of antigen-specific therapies remains ambiguous. Larger, well-designed studies with high level quality are needed to ensure ultimate conclusions. REGISTRATION: The registration number provided following registration of the protocol in PROSPERO is 'CRD42021236776'.
Keywords: lidé; Multiple Sclerosis; Antigens; antigeny; roztroušená skleróza; Treatment Outcome; výsledek terapie; Humans